PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN BERPIKIR KOMPUTASI SISWA - Fadhilah Nur Sa’diyyah; Sitti Mania; Suharti Suharti (IKIP Siliwangi, 2021)
Mathematics learning in the 2013 curriculum emphasizes the pedagogic dimension which aims to create active students so that they are able to develop their mindset and accustom them to finding solutions to their own problems. This research aims to develop test instrumen to measure computational thinking on number and sequence pattern material in SMP Negeri 2 Sungguminasa that meets valid and practical criteria. The purpose of this study was to determine the process of developing test instrumen to measure computational thinking on number and sequence pattern material in SMP Negeri 2 Sungguminasa. This research is a type of Research and Development (R&D) that focused on development model of B&G (Borg & Gall) which contains 4 stages: the information gathering stage, the planning stage, the development stage, validation and trial stage. The subjects of the trial were students of class VIII SMP Negeri 2 Sungguminasa. The instruments used in this study were the validation sheet and the teacher response questionnaire. Based on the Results of the study, it was found that (1) the validation results for test instrumen to measure computational thinking were 4,46 so that they only uses a teacher response questionnaire for all aspects in the very positive category with a percentage of 90,6%. So it can be concluded that test instrumen to measure computational thinking on number and sequence pattern material in SMP Negeri 2 Sungguminasa meet the validity and practicality criteria.